Green Transformation of Individual Transport - Current State of Electromobility - Case Study in Poland - Jaromir MYSŁOWSKI; Wojciech LEWICKI (Communications of International Proceedings, 2023)
The available literature on the subject emphasizes that green transport based on the idea of electromobility is an inevitable process. The Electromobility Development Program is to become one of the pillars of the Plan for responsible economic development of each country. Its effect is to create conditions for the development of production and popularization of electric vehicles. According to the assumptions of the Polish Ministry of Energy, 1 million electric vehicles are to appear on Polish roads by 2025. The aim of the article is to present the current challenges related to the implementation of this ambitious plan in this difficult economic and social period. Therefore, the article uses the method of observing the state of development of electromobility in relation to the demand and supply sides. In particular, an attempt was made to identify the basic barriers and possible benefits related to the operation of electric vehicles at the end of 2023. This research may contribute to faster development of universal solutions for eliminating existing restrictions and barriers by identifying areas requiring adaptation to new market rules. Additionally, the presented analyzes and diagnoses of the current state can constitute the basis and encouragement for further research on topics related to the promotion of green transport through the development of electromobility in terms of identifying further consequences for all stakeholders of this market.
Keywords: green transformation; electromobility; automotive sector; market research; state policy